Simulation and Experimental Study of Tensile Strength of Ukam Fibre Reinforced Polyester Composites using ANSYS - Okpanachi, G. E.; Hassan, A. S.; Ahmed, El – M. A.; Hussein, S. U.; Alapa, F. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Polymers are commonly used in different applications even though it causes environmental problems. Natural fibre reinforced composites can be used as substitute for the synthetic fibre composites because of their biodegradable properties which will be a key to solving environmental problems although, the strength of natural fibres is not as high as glass fibres, their specific properties are comparable. The hand lay–up method of fabrication was employed in preparing the composite. This study investigates the tensile strength of the composite using experimental and numerical method. The test specimen of natural composite was fabricated using ASTM standard and the tensile strength of the composite determined using Hounsfield Tensometer. A 3D Finite Element (FE) model was created to simulate tensile strength in ANSYS 18. Alkali treated samples exhibited the highest increase in tensile strength at all fibre loadings. Modulus of elasticity (MOE) and percentage elongation also increased with increase in fibre loading for all treatments. The experimental values of tensile strength at 25 % were in agreement with the FEM tensile strength using ANSYS.